Composite lithium supplementing material and preparation method thereof, positive electrode material and secondary battery

By designing a composite structure with pores in the lithium-supplementing material, and using the second functional material of the porous structure to contain and absorb gas, the problems of high gas production and high interfacial activity of the existing lithium-supplementing materials are solved, and the life of the lithium-ion battery is improved. and security.

CN119361707APending Publication Date: 2025-01-24SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411559363.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing lithium supplementary materials have problems such as high gas production, high interface activity and poor air stability, resulting in a shortened life and reduced safety of lithium-ion batteries.

Method used

A composite lithium-supplementing material is provided, which includes a lithium-rich material, a first functional material and a second functional material. The first functional material has pores inside, and the second functional material has a porous structure and is contained in the pores to reduce gas escape.

Benefits of technology

By reducing the gas generated after discharge of lithium -enriched materials, reducing the risk of battery's volume expansion, increasing the life and safety of the battery, and protecting the lithium -rich material to avoid side reactions with electrolytes or air.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361707A_ABST
    Figure CN119361707A_ABST
Patent Text Reader

Abstract

The invention discloses a composite lithium supplementing material and a preparation method thereof, a positive electrode material and a secondary battery, the composite lithium supplementing material comprises a lithium-rich material, a first functional material and a second functional material, the first functional material is internally provided with a pore channel, and the pore channel extends to the outer surface of the first functional material and forms an opening; the second functional material and at least part of the lithium-rich material are contained in the pore channel, the second functional material is of a porous structure, and the second functional material is arranged between the lithium-rich material and the opening of the pore channel. The composite lithium supplementing material provided by the invention has the characteristics of low gas production rate and high structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery. Background Art

[0002] During the first charge and discharge process of lithium-ion batteries, the Li + Reacting with the electrolyte, a solid electrolyte interface (SEI) will be formed on the surface of the negative electrode material. This process will irreversibly consume more than 10% of the lithium source in the positive electrode material, making the first week coulomb efficiency less than 90%, and will continue to consume the active lithium in the positive electrode during the charge and discharge cycle of the lithium battery, resulting in a shortened life of the lithium-ion battery. In response to this phenomenon, the current solution is to add appropriate lithium supplement materials to the positive electrode material, and reduce the lithium loss during the cycle by releasing active lithium through the decomposition of the lithium supplement material during the battery charging process.

[0003] However, existing lithium-supplementing materials have the problems of high gas production, high interfacial activity and poor air stability. Summary of the invention

[0004] The purpose of the present application is to provide a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery, so as to solve the problems of high gas production, high interfacial activity and poor air stability of existing lithium supplement materials.

[0005] To achieve the purpose of this application, this application provides the following technical solutions:

[0006] In a first aspect, the present application provides a composite lithium-supplementing material, comprising a lithium-rich material, a first functional material and a second functional material, wherein the first functional material has a pore inside, the pore extending to the outer surface of the first functional material and forming an opening, the second functional material and at least part of the lithium-rich material are accommodated in the pore, the second functional material is a porous structure, and the second functional material is arranged between the lithium-rich material and the opening of the pore.

[0007] In one embodiment, the pore size of the pores gradually decreases from the inside of the first functional material to the outside of the first functional material.

[0008] In one embodiment, there are a plurality of pores, and at least two of the pores have different pore diameters, and the particle sizes of the lithium-rich materials contained in the pores with different pore diameters are different.

[0009] In one embodiment, the same pore channel includes at least two lithium-rich materials, and the two lithium-rich materials are of different types and / or particle sizes.

[0010] In one embodiment, the core comprises a lithium-rich material, the composite lithium-supplementing material further comprises a core, the first functional material is coated on the outer layer of the core, and the core comprises one or more of a lithium-rich material, a catalytic material, and a supporting material.

[0011] In one embodiment, the lithium-rich material contained in the pores is a first lithium-rich material, and the lithium-rich material formed in the inner core is a second lithium-rich material, and the second lithium-rich material is of a different type from the first lithium-rich material.

[0012] In one embodiment, the mass ratio of the first lithium-rich material to the second lithium-rich material is in the range of (50-95): (5-50).

[0013] In one embodiment, the inner diameter of the pores ranges from 10 nm to 100 nm.

[0014] In one embodiment, the particle size of the second functional material is in the range of 1 nm to 50 nm.

[0015] In one embodiment, the second functional material is at least partially adhered to the sidewall of the channel.

[0016] In one embodiment, the porosity of the second functional material is 20% to 60%.

[0017] In one embodiment, the expansion rate of the second functional material is 150% to 300%.

[0018] In one embodiment, the second functional material includes one or more of silicon materials, carbon materials, polymer materials, and gel materials.

[0019] In one embodiment, the particle size D50 of the inner core is 100 nm to 500 nm.

[0020] In one embodiment, the thickness of the first functional material coated on the outer surface of the inner core is 100 nm to 1500 nm.

[0021] In one embodiment, the first functional material includes carbon material and / or metal oxide.

[0022] In one embodiment, the porosity of the first functional material is 5% to 40%.

[0023] In one embodiment, the mass ratio of the lithium-rich material, the first functional material and the second functional material is (20-80): (10-79): (1-10).

[0024] In the second aspect, the present application provides a method for preparing a composite lithium-supplementing material, comprising the following steps: coating a first functional material on the outside of a template material, and then removing the template material to obtain a first functional material having pores, wherein the pores extend to the outer surface of the first functional material and form openings; sequentially mixing and sintering the first functional material and a lithium-rich material precursor and a second functional material precursor so that the lithium-rich material precursor and the second functional material precursor enter the pores and are converted into lithium-rich material and second functional material, respectively, wherein the second functional material is a porous structure, and the second functional material is arranged between the lithium-rich material and the opening of the pores.

[0025] In a third aspect, the present application further provides a positive electrode material, which includes a positive electrode active material and a lithium supplement agent, wherein the lithium supplement agent includes the composite lithium supplement material described in the first aspect, or the positive electrode material includes a lithium supplement material obtained by the preparation method of the composite lithium supplement material described in the second aspect.

[0026] In a fourth aspect, the present application further provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material described in the third aspect.

[0027] In one embodiment, after the secondary battery is charged and discharged for the first time, in the composite lithium supplement material, the outer surface of the second functional material is in contact with the side wall of the pore.

[0028] In response to the problems existing in the prior art, the present application provides a composite lithium-supplementing material with a pore structure, and the composite lithium-supplementing material has the following effects: 1) The lithium-rich material is contained in the pore, and the pore provides a containing space for the gas generated after the lithium-rich material is discharged, which can prevent the gas from escaping directly into the electrolyte; 2) The second functional material is also contained in the pore, and the second functional material can reduce the size of the pore opening compared to the opening of the lithium-rich material close to the pore, thereby limiting the escape of gas from the opening of the pore; 3) The second functional material is a porous structure, and the pores of the second functional material can be used to absorb gas, thereby achieving the purpose of further reducing gas production, and ultimately reducing the risk of battery volume expansion; 4) The first functional material can provide structural support for the composite lithium-supplementing material to prevent the lithium-rich material from shrinking in volume or pulverizing after decomposition due to lithium removal, resulting in pits or cracks in the pole piece; 5) The first functional material and the second functional material can also protect the lithium-rich material to prevent the lithium-rich material from producing side reactions with the electrolyte or air. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 is a schematic diagram of the cross-sectional structure of a composite lithium supplement material according to an embodiment;

[0031] Figure 2 is a schematic diagram of a partial cross-sectional structure of a composite lithium supplement material according to an embodiment;

[0032] Figure 3 is a schematic diagram of a partial cross-sectional structure of a composite lithium supplement material according to another embodiment;

[0033] Figure 4 is a schematic diagram of a partial cross-sectional structure of a composite lithium supplement material according to another embodiment;

[0034] Figure 5 is a schematic diagram of the interface structure of a core and a template material in one embodiment;

[0035] Figure 6 The present invention is a flow chart of a method for preparing a composite lithium supplement material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0037] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.

[0038] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0039] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0040] This application provides a composite lithium supplement material, please refer to Figure 1 .

[0041] In one embodiment, the composite lithium-supplementing material includes a first functional material 10, a lithium-rich material 20 and a second functional material 30. The first functional material 10 has a pore inside, and the pore 11 extends to the outer surface of the first functional material 10 and forms an opening. The second functional material 30 and at least part of the lithium-rich material 20 are accommodated in the pore 11. The second functional material 30 is a porous structure, and the second functional material 30 is arranged between the lithium-rich material 20 and the opening of the pore 11.

[0042] Specifically, the lithium-rich material 20 is the main body for lithium supplementation, which can contribute a large amount of lithium ions. During the first charging process, the lithium (Li) in the lithium-rich material can be released and migrated to the negative electrode of the battery to offset the irreversible lithium loss caused by the formation of the SEI film, thereby improving the total capacity and energy density of the battery. However, most of the existing commonly used lithium-rich materials have problems such as high interfacial activity, high gas production, and high surface residual alkali. The above problems will lead to limited application of lithium-rich materials in the positive electrode. For example, high interfacial activity and high surface residual alkali will cause the lithium-rich material to produce side reactions with the electrolyte or air, affecting the battery performance, and the high gas production of the lithium-rich material will lead to the safety problem of battery volume expansion. So how to solve the above problems has become the key.

[0043] In view of the problems existing in the prior art, the present application provides a composite lithium supplement material with a pore 11 structure, and the composite lithium supplement material has the following effects: 1) the lithium-rich material 20 is contained in the pore 11, and the pore 11 provides a containing space for the gas generated by the lithium-rich material 20 after discharge, which can prevent the gas from escaping directly into the electrolyte; 2) the second functional material 30 is also contained in the pore 11, and the second functional material 30 is closer to the opening of the pore 11 than the lithium-rich material 20, and the second functional material 30 can reduce the size of the opening of the pore 11, thereby limiting the gas from escaping from the pore 11. 1; 3) The second functional material 30 is a porous structure, and the pores of the second functional material 30 can be used to absorb gas, thereby achieving the purpose of further reducing gas production, and ultimately reducing the risk of battery volume expansion; 4) The first functional material 10 can provide structural support for the composite lithium supplement material to prevent the lithium-rich material 20 from shrinking in volume or pulverizing after delithiation, resulting in pits or cracks in the electrode; 5) The first functional material 10 and the second functional material 30 can also protect the lithium-rich material 20 to prevent the lithium-rich material 20 from producing side reactions with the electrolyte or air.

[0044] In one embodiment, the chemical formula of the lithium-rich material 20 includes Li x1 M y1 O z1 , where M is at least one element among Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, Sn, etc., 1 ≤ x1 ≤ 8, 0 < y1, 0 < z1 < 7. In a specific embodiment, the lithium-rich material 20 may include at least one of Li5FeO4, Li6MnO4, Li6CoO4, Li6ZnO4, Li2NiO2, Li2CuO2, Li2CoO2, Li2MnO2, Li2Ni 0.5 Mn 1.5 O4, Li2Ni d Cu (1-d) O2(0 < d < 1), etc. It can be understood that since the above lithium-rich material 20 includes transition metals, residual alkali is likely to form on the material surface, and gas will be generated after the material is discharged. Therefore, the solution provided in this application is applicable to such materials.

[0045] In one embodiment, the chemical formula of the lithium-rich material 20 includes Li x2 C y2 O z2 , where 0 < x2 ≤ 2, y2 > 0, z2 > 0. In a specific embodiment, the lithium-rich material 20 may include one or more of Li2C2O4 (lithium oxalate), Li2CO3 (lithium carbonate), Li2C3O3 (lithium trioxalate), Li2C4O4 (lithium butynedioate), Li2C6O6, Li2C3O5 (lithium pyruvate), and Li2C4O6. It can be understood that the above lithium-rich materials 20 are all materials with a high decomposition voltage. A higher voltage will cause oxygen to be generated during the first charge and discharge of the lithium-ion battery, and the generated oxygen will further oxidize and cause the electrolyte to oxidize and decompose, resulting in a reduction in the safety and performance of the lithium-ion battery. Therefore, the solution provided in this application is applicable to such materials.

[0046] In one embodiment, the chemical formula of the lithium-rich material 20 includes Li x3 K y3 , where K is at least one element among O, S, P, N, F, B, Se, Te, 1 ≤ x3 ≤ 5, 0 < y3. The binary lithium supplementing agent includes but is not limited to at least one of Li2O, Li2O2, Li3N, Li2S, LiF, Li3P, Li2Se. It can be understood that the above lithium-rich material 20 is a binary lithium supplementing agent, and most of them have problems of poor conductivity and poor stability, and are prone to react with air or water vapor to decompose or generate gas. Therefore, the solution provided in this application is applicable to such materials.

[0047] In one embodiment, the chemical formula of the lithium-rich material 20 includes Li 1+x4 A y4 O z4 , where 0 <x4≤1.2,1≤y4<3,z4> 0, A includes at least one of Ni, Fe, Mn, Co, Cr, V, Mo, Ti, Nb, Zr, Cu, and Mg. The lithium-rich materials 20 can be used as lithium supplements or directly as positive electrode materials. Exemplarily, the lithium-rich material 20 includes at least one of Li2CuO2, Li2NiO2, and Li2MnO2.

[0048] In one embodiment, the lithium-rich material 20 may also include LiOH (delithiation potential 4.8V), Li4SiO4 (delithiation potential 4.5V), and Li3PO4 (delithiation potential exceeding 4V). These materials require a higher charging voltage for delithiation, which will cause the lithium-ion battery to produce oxygen during the first charge and discharge. The generated oxygen is further oxidized to cause the electrolyte to oxidize and decompose, thereby reducing the safety and performance of the lithium-ion battery. Therefore, the solution provided in this application can be applied to such materials.

[0049] In one embodiment, the lithium-rich material 20 mentioned above may be undoped or modified by doping, or may be surface coated, pre-lithiated, etc. These lithium-rich materials 20 have high theoretical capacity and structural stability, can provide sufficient lithium ions, effectively supplement the irreversible lithium ions consumed by the formation of SEI film at the negative electrode, and improve the initial efficiency and overall electrochemical performance of the battery.

[0050] In one implementation, please refer to Figure 1 , the outer contour of the first functional material 10 can be spherical, three-dimensional or polyhedral. A pore 11 is formed inside the first functional material 10, and the pore 11 extends to the outer surface of the first functional material 10, so that the pore 11 and the external space of the first functional material 10 are connected. Optionally, the first functional material 10 includes a carbon material and / or a metal oxide, and the specific first functional material 10 can be graphene, hard carbon / soft carbon, aluminum oxide, titanium dioxide, etc. And making the first functional material 10 into a spherical or polyhedral shape is also conducive to the extension of the pore 11 and improves the porosity of the first functional material 10.

[0051] In one embodiment, the outer contour of the first functional material 10 can be spherical, and the pores 11 extend straight or curved from the center of the first functional material 10 to the outer surface. In addition, there can be multiple pores 11, and the multiple pores 11 are independent of each other, and the multiple pores 11 can be radially distributed inside the first functional material 10, and the radial distribution of the pores 11 means that the center of the first functional material 10 is used as the origin and then extends radially to the surroundings. Multiple radially distributed pores 11 increase the porosity of the first functional material 10, thereby improving the ability of the first functional material 10 to accommodate the lithium-rich material 20, thereby improving the capacity of the composite lithium-supplementing material.

[0052] In one implementation, please refer to Figure 1 and Figure 2 , the lithium-rich material 20 and the second functional material 30 are both contained in the pore 11, and the second functional material 30 is closer to the opening of the pore 11 (that is, closer to the outer surface of the first functional material 10), and the second functional material 30 is used to reduce the opening size of the pore 11. Optionally, in the pore 11, the sum of the volumes of the lithium-rich material 20 and the second functional material 30 is smaller than the volume of the pore 11, that is, the lithium-rich material 20 and the second functional material 30 do not completely fill the pore 11. Setting the sum of the volumes of the first lithium material and the second functional material 30 smaller than the volume of the pore 11 can allow some space to be retained in the pore 11, and the space in the pore 11 can be used to accommodate the gas generated by the lithium-rich material 20 after discharge, and under the blocking of the second functional material 30, the gas in the pore 11 will not escape, thereby reducing the gas production of the composite lithium supplement material.

[0053] In one embodiment, the second functional material 30 is a nanoporous material with pores, and the second functional material 30 has an expandable property. Specifically, the second functional material 30 has nanoscale or sub-nanoscale pores, and the pores are used to absorb the gas generated after the lithium-rich material 20 is delithiated, and the second functional material 30 can expand (increase in volume) after absorbing the gas. In a specific embodiment, the second functional material 30 can be a porous silicon material, and the porous silicon material itself has an expandable property.

[0054] In one embodiment, the second functional material 30 may be a composite material composed of multiple materials, a core-shell structure composed of multiple materials, or a homogeneous structure formed by a simple mixture of multiple materials. Figure 3The second functional material 30 may include a pore portion 31 and an expansion portion 32, wherein the pore portion 31 is a porous structure and the expansion portion 32 has expandable properties. The holes in the pore portion 31 are used to absorb gas, and the expansion portion 32 is used to expand. Of course, the factors that cause the expansion portion 32 to expand are not limited to the expansion of the accommodating gas, and may also include the expansion of the expansion portion 32 due to heat or the expansion of the expansion portion 32 due to charging. The pore portion 31 and the expansion portion 32 may independently include different materials, so as to form holes and have expandability respectively.

[0055] In one embodiment, if Figure 3 As shown, the pore portion 31 is close to the lithium-rich material 20, and the expansion portion 32 is far away from the lithium-rich material 20 (i.e., close to the opening). The pore portion 31 is close to the lithium-rich material 20, so that the gas generated by the lithium-rich material 20 can be quickly absorbed by the pore portion 31, and after the pore portion 31 absorbs the gas, the expansion portion 32 expands to block the opening of the pore 11.

[0056] In one embodiment, if Figure 3 As shown, the second functional material 30 is at least partially attached to the side wall of the pore 11. Specifically, the pore portion 31 may be attached to the side wall of the pore 11, and there is a gap between the expansion portion 32 and the side wall of the pore 11 (the lithium-rich material 20 is not in a state of charge and discharge). It should be explained that there is a gap between the expansion portion 32 and the side wall of the pore 11, thereby providing space for the expansion portion 32 to expand, and preventing the side wall of the pore 11 from limiting the expansion of the expansion portion 32.

[0057] In one embodiment, the second functional material 30 has continuity in the pores 11, and part of the second functional material 30 can be connected to the lithium-rich material 20. It can be understood that the second functional material 30 is used to absorb gas and expand, so the connection between the second functional material 30 and the lithium-rich material 20 can increase the rate at which gas is absorbed into the second functional material 30.

[0058] It should be noted that the second functional material 30 provided in the present application is different from some packaging materials or coating materials in the prior art. The initial state of the second functional material 30 (the state in which the lithium-rich material 20 is not charged or discharged) can be a state without expansion, and the second functional material 30 can be partially fitted with the side wall of the pore 11, so in the initial state, the second functional material 30 is mainly used to reduce the opening size of the pore 11, thereby avoiding direct contact and reaction between the lithium-rich material 20 and the electrolyte, air or water vapor. Then, after the lithium-rich material 20 is delithiated, the lithium-rich material 20 generates gas, and the gas is absorbed by the pores of the second functional material 30. The second functional material 30 expands under the action of the gas, so that the outer surface of the second functional material 30 is completely fitted with the side wall of the pore, thereby blocking the pore; so the gas that continues to be generated by the lithium-rich material 20 will not escape. In addition, since the expansion of the second functional material 30 supports the first functional material 10, the structural stability of the composite lithium supplement material is improved, which can further reduce the phenomenon of pits in the pole piece caused by the reduction of the material volume or pulverization.

[0059] In one implementation, please refer to Figure 1 and Figure 2 , the aperture of the pore 11 gradually decreases from the inside of the first functional material 10 to the outside of the first functional material 10. Specifically, the aperture of the pore 11 does not limit the cross-section shape of the pore 11 to only a circle. Of course, the cross-section shape of the pore 11 can also be an ellipse, a polygon, etc., without specific restrictions. From the inside of the first functional material 10 to the outside of the first functional material 10, the change rule of the gradual decrease of the aperture of the pore 11 can be a uniform linear decrease, or the aperture of a certain section of the pore 11 remains unchanged, and the aperture of a certain section of the pore 11 decreases, preferably a uniform linear decrease. The present application sets the aperture of the pore 11 to gradually decrease, so as to facilitate the suppression of gas escape, because the opening of the pore 11 on the outer surface of the first functional material 10 is smaller, and the gas escape is more difficult; and, because the aperture at the opening of the pore 11 is smaller, the proportion of the second functional material 30 required to be used is also smaller, so that it will not affect the proportion of the lithium-rich material 20, and ensure the lithium replenishment capacity of the composite lithium replenishment material.

[0060] In one implementation, please refer to Figure 1 and Figure 2, the contour shape of the pore 11 is conical, the larger end of the cone is located inside the first functional material 10, and the smaller end of the cone is close to the outer surface of the first functional material 10, so the pore size of the pore 11 gradually decreases from the inside of the first functional material 10 to the outside of the first functional material 10. It can be understood that, based on the above embodiment, the second functional material 30 is located at the smaller pore size of the pore 11, and the lithium-rich material 20 is located at the larger pore size of the pore 11. The conical pore 11 has the characteristics of uniform linear reduction, which makes the structure of the first functional material 10 more stable, and the preparation difficulty of the conical pore 11 is relatively small during the preparation process, and the pore size of the pore 11 is controllable.

[0061] In one embodiment, the opening diameter on the outer surface of the first functional material 10 is not larger than the diameter of the corresponding pore 11. It should be explained that the contour shape of the pore 11 can also be other shapes, but the pore 11 has the smallest diameter at the corresponding opening, such as gourd shape, pear shape, polyhedron shape, etc. (please refer to Figure 4 It is understandable that setting the opening diameter of the channel 11 at the outer surface to be smaller is conducive to the effective blocking of the expanded second functional material 30, and can avoid the situation where the second functional material 30 cannot block the opening when its own expansion rate is small.

[0062] In one implementation, please refer to Figure 1 and Figure 2 , there are multiple channels 11, and at least two channels 11 have different pore sizes, and the particle sizes of the lithium-rich material 20 contained in the channels 11 with different pore sizes are different. Specifically, in the first functional material 10, the multiple channels 11 are arranged radially, and preferably the pore sizes of the channels 11 are not all the same. It should be explained that the different pore sizes of the channels 11 means that, based on the maximum pore size of the channel 11, at least two channels 11 have different pore sizes at their maximum points; for example, Figure 2 As shown, the first functional material 10 includes a channel 11A and a channel 11B, wherein the channel 11A and the channel 11B are relatively independent, the maximum aperture of the channel 11A is R1, the maximum aperture of the channel 11B is R2, and R1≠R2. In the present application, a plurality of radial channels 11 with different apertures are provided in the first functional material 10, which can accommodate lithium-rich materials 20 of different particle sizes (for example, two different lithium-rich materials 20 are accommodated in channels 11 with different apertures), so as to adjust the decomposition voltage and decomposition rate of the lithium-rich material 20, and can also help to compound the lithium-rich materials 20 with different conductivity and decomposition voltage, etc.

[0063] In one embodiment, the same channel 11 includes at least two lithium-rich materials 20, and the types and / or particle sizes of the two lithium-rich materials 20 are different. Specifically, the lithium-rich material 20 may include two types, that is, two different lithium-rich materials 20 are contained in the first functional material 10. In a specific embodiment, the lithium-rich material 20 may include a lithium-rich material Li x1 C y1 O z1 , and lithium-rich materials Li x3 M y3 O z3 It is understood that in the pores 11 of the first functional material 10, the type of the lithium-rich material 20 is not limited, and different lithium-rich materials 20 can be selected for filling different first functional materials 10 and second functional materials 30. In other specific embodiments, the lithium-rich material 20 may include two lithium-rich materials Li with different particle sizes. x1 C y1 O z1 Based on the above implementation, Li x1 C y1 O z1 It can be located deeper in the pore 11 and has a smaller particle size. x1 C y1 O z1 It can be close to the opening of the channel 11.

[0064] In one implementation, please refer to Figure 1 , the composite lithium-supplementing material also includes a core 40, a first functional material 10 is coated on the outer layer of the core 40, and a pore 11 extends from the outer surface of the core 40 to the outside of the first functional material 10, and the core 40 contains one or more of a lithium-rich material, a catalytic material, and a supporting material. Specifically, the composite lithium-supplementing material is a core-shell structure, including a core 40 and a coating layer coated on the outer surface of the core 40, and the coating layer includes a first functional material 10, part (or all) of a lithium-rich material 20, and a second functional material 30. Among them, the outer surface of the core 40 is mainly covered by the first functional material 10, and the first functional material 10 is formed with the pore 11 described above. The present application also sets a core 40 in the first functional material 10, and the core 40 can be used to support the first functional material 10, and can also be used to assist the first functional material 10 in making the pore 11 inside it.

[0065] It should be noted that the lithium-rich material contained in the core 40 can be the same as or different from the lithium-rich material in the pores 11 of the coating layer. In this embodiment, the lithium-rich material 20 in the composite lithium supplementing material can be divided into two parts. The lithium-rich material contained in the core 40 and the lithium-rich material in the pores 11 only refer to two parts of lithium-rich materials with different spatial positions, rather than a limitation on their types. The catalytic material can be a material that can catalyze the lithium-rich material 20, such as a transition metal compound, etc.; the supporting material can be a material with chemical stability, such as metallic silver, etc.

[0066] In one embodiment, the pores 11 in the first functional material 10 are made by a template material. Specifically, the template material can be first made on the outer surface of the core 40, and then the shape of the template material is set to be conical or a constricted cylindrical shape. The template material is distributed on the outer surface of the core 40 in the form of multiple cones or cylinders. Then the first functional material 10 is covered on the core 40 and the template material, and the template material is removed. Thus, the part where the template material is removed forms the pores 11.

[0067] In one embodiment, the core 40 contains a lithium-rich material. The lithium-rich material accommodated in the pores 11 is the first lithium-rich material, and the lithium-rich material formed in the core 40 is the second lithium-rich material. The second lithium-rich material is different from the first lithium-rich material in type. Specifically, the chemical formulas of the first lithium-rich material and the second lithium-rich material can refer to those provided by the above-mentioned lithium-rich material 20. Among the various lithium supplementing agents provided by the above-mentioned lithium-rich material 20, the type of the second lithium-rich material can be the same as that of the first lithium-rich material, that is, the chemical formulas of the second lithium-rich material and the first lithium-rich material are the same (including element composition and element content); of course, the type of the second lithium-rich material can be different from that of the first lithium-rich material, that is, the chemical formulas of the second lithium-rich material and the first lithium-rich material are different.

[0068] In one embodiment, both the first lithium-rich material and the second lithium-rich material are lithium-rich materials containing transition metals, and the chemical formula is Li x1 M y1 O z1 , where 1 ≤ x1 ≤ 8, 0 < y1, 0 < z1 < 7, and the transition metal elements contained in the first lithium-rich material and the second lithium-rich material are not all the same. The first lithium-rich material can specifically include Li2NiO2, Li5FeO4, Li6MnO4, Li6CoO4, Li6ZnO4, Li2CuO2, Li2CoO2, Li2MnO2, Li2Ni 0.5 Mn 1.5 O4, Li2Ni d Cu (1-d)One or more of O2 (0 < d < 1), etc., the second lithium-rich material may include one or more of the above materials, and preferably the second lithium-rich material may be Li5FeO4 and / or Li6CoO4.

[0069] This application does not limit the material of the inner core 40. When the inner core 40 includes the second lithium-rich material, the inner core 40 can also provide an additional lithium supplement capacity, so that the first lithium-rich material and the second lithium-rich material cooperate to regulate the decomposition voltage and decomposition rate of the lithium-rich material; in addition, the inner core 40 can also include metal compounds (such as metal oxides, etc.), and such compounds can be used as catalysts to catalyze some lithium-rich materials 20 with high decomposition voltages (such as lithium carbonate) to reduce the decomposition voltage, which can not only improve the lithium supplement capacity but also reduce gas production.

[0070] In one embodiment, the mass ratio range of the first lithium-rich material to the second lithium-rich material is (50 - 95):(5 - 50). Meeting the mass ratio of the first lithium-rich material to the second lithium-rich material within the above range can ensure the number of pores and control the thickness of the coating layer. When the proportion of the second lithium-rich material is too small, the particle size of the inner core is too small, resulting in a relatively small number of pores. When the proportion of the second lithium-rich material is too large, the overall particle size of the composite lithium supplement material is too large, or the thickness of the coating layer is too small, which is not conducive to lithium ion release or gas production control. Optionally, the mass ratio of the first lithium-rich material to the second lithium-rich material can be 50:50, 55:45, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, 95:15.

[0071] In one embodiment, the inner diameter range of the pore 11 is 10 nm to 100 nm. Meeting the inner diameter of the pore 11 within the above range can ensure the lithium supplement capacity, and ensure that the second functional material 30 can completely block the pore 11 after expansion, as well as the structural stability of the first functional material 10. When the inner diameter of the pore 11 is too small, the content of the lithium-rich material 20 accommodated in the pore 11 is less, and the lithium supplement capacity of the composite lithium supplement material is affected. When the inner diameter of the pore 11 is too large, it is difficult for the second functional material 30 to completely block the pore 11 after expansion, and the structural stability of the first functional material 10 becomes poor, and the overall strength of the composite lithium supplement material becomes poor. Optionally, the inner diameter of the pore 11 can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm.

[0072] In one embodiment, the particle size range of the second functional material 30 is 1nm to 50nm. It should be explained that the particle size range of the second functional material 30 should be the particle size before expansion, and the particle size after expansion should be adapted to the inner diameter of the pore 11. Meeting the particle size of the second functional material 30 within the above range can ensure that the second functional material 30 has a sufficient expansion size to achieve a plugging effect. When the particle size of the second functional material 30 is too small, the second functional material 30 cannot achieve the effect of plugging the pore 11 even if it expands. Optionally, the particle size of the second functional material 30 can be 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm.

[0073] In one embodiment, the porosity of the second functional material 30 is 20% to 60%. When the porosity of the second functional material 30 is within the above range, the structural stability of the second functional material 30 and the expansion volume change effect can be ensured. When the porosity of the second functional material 30 is too small, the gas absorbed by the second functional material 30 is limited, resulting in a small volume expansion of the material, and the pores 11 cannot be fully blocked. When the porosity of the second functional material 30 is too large, the structural stability of the second functional material 30 deteriorates, and a small amount of gas will escape through some pores. Optionally, the porosity of the second functional material 30 can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%.

[0074] In one embodiment, the expansion rate of the second functional material 30 is 150% to 300%. When the expansion rate of the second functional material 30 is within the above range, it can be ensured that the second functional material 30 has a strong expansion ability to block the pores 11. When the expansion rate of the second functional material 30 is too small, the second functional material 30 absorbs gas but is difficult to expand, resulting in a poor blocking effect of the second functional material 30 on the pores 11. Optionally, the expansion rate of the second functional material 30 can be 150%, 200%, 250%, or 300%.

[0075] In one embodiment, the second functional material 30 includes one or more of silicon material, carbon material, polymer material, and gel material. Among them, the carbon material can be graphene, porous carbon, expanded graphite, etc. Optionally, the second functional material 30 can be a porous silicon material, such as porous silica, porous silicon, etc. The advantage of selecting silicon material as the second functional material 30 is that the porous silicon material can absorb the gas generated by the lithium-rich material 20 to expand the volume, block the opening of the pore 11 in situ, absorb the gas on the one hand, and restrict the gas in the pore 11 on the other hand. Of course, the second functional material 30 can be a polymer material, because the polymer material has a swelling effect (referring to the phenomenon that the volume of a polymer expands in a solvent), and can expand when immersed in an electrolyte. At the same time, the second functional material 30 can be a gel material, and the colloidal particles or polymers of the gel material are interconnected under certain conditions to form a spatial network structure, thereby forming a porous structure, which can expand by absorbing gas or electrolyte.

[0076] In one embodiment, the particle size D50 of the core 40 is 100nm to 500nm. When the particle size D50 of the core 40 is within the above range, the proportion of the lithium-rich material 20 and the overall particle size of the composite lithium-supplementing material can be ensured to ensure that the composite lithium-supplementing material has a large lithium-supplementing capacity and high physical and chemical properties. When the particle size D50 of the core 40 is too small, it will increase the difficulty of making the pores 11 using the template, the number of pores 11 will decrease, and the proportion of the lithium-rich material 20 will decrease. When the particle size D50 of the core 40 is too large, the overall particle size of the composite lithium-supplementing material will be too large, which is not conducive to the release of lithium ions. Optionally, the particle size D50 of the core 40 can be 100nm, 200nm, 300nm, 400nm, or 500nm.

[0077] In one embodiment, the thickness of the first functional material 10 coated on the outer surface of the core 40 is 100nm to 1500nm. When the thickness of the first functional material 10 is within the above range, the length of the pore 11 can be guaranteed to ensure the proportion of the lithium-rich material 20 and the structural stability of the first functional material 10. When the thickness of the first functional material 10 is too small, the length of the pore 11 will also be too short, resulting in a reduction in the proportion of the lithium-rich material 20. When the thickness of the first functional material 10 is too large, the coating will be too thick, resulting in a larger overall particle size of the composite lithium-supplementing material, which is not conducive to the release of lithium ions. Optionally, the thickness of the first functional material 10 coated on the outer surface of the core 40 can be 100nm, 300nm, 500nm, 700nm, 900nm, 1100nm, 1300nm, 1500nm.

[0078] In one embodiment, the mass ratio of the core 40 and the first functional material 10 is (5-30): (70-95). When the mass ratio of the core 40 and the first functional material 10 is within the above range, it can be ensured that the composite lithium supplement material has a large lithium supplement capacity and a strong conductivity. When the mass ratio of the first functional material 10 is too small, the thickness of the first functional material 10 is also small, resulting in a reduction in the proportion of the lithium-rich material 20 and a decrease in the conductivity provided by the first functional material 10. When the mass ratio of the first functional material 10 is too large, the coating is too thick, which will cause the overall particle size of the composite lithium supplement material to be larger, and will also cause the core 40 to be smaller and the number of channels 11 to be reduced. Optionally, the mass ratio of the core 40 and the first functional material 10 can be 30:70, 25:75, 20:80, 15:85, 10:90, 5:95.

[0079] In one embodiment, the porosity of the first functional material 10 is 5% to 40%. When the porosity of the first functional material 10 is within the above range, the richness of the pores 11 can be ensured, that is, the composite lithium supplement material has a large lithium supplement capacity, and the structural stability of the first functional material 10 can be ensured. When the porosity of the first functional material 10 is too small, the number of pores 11 is too small or the length of the pores 11 is too short, resulting in a small content of the lithium-rich material 20 contained in the pores 11, and the lithium supplement capacity of the composite lithium supplement material is affected. When the porosity of the first functional material 10 is too large, the structural stability of the first functional material 10 deteriorates, and the overall strength of the composite lithium supplement material deteriorates. Optionally, the porosity of the first functional material 10 can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, or 40%.

[0080] In one embodiment, the mass ratio of the lithium-rich material 20, the first functional material 10 and the second functional material 30 is (20-80): (10-79): (1-10). It should be noted that the lithium-rich material 20 in this mass ratio is the first lithium-rich material in the above embodiment. When the mass ratio of the above three is within the above range, it can be ensured that the composite lithium-supplementing material has a large lithium-supplementing capacity, as well as the conductivity of the material and the lower gas production. When the mass proportion of the first functional material 10 or the second functional material 30 is too large, the content of the lithium-rich material 20 will be affected, thereby reducing the lithium-supplementing capacity of the composite lithium-supplementing material. When the mass proportion of the first functional material 10 is too small, it will affect the storage capacity of the lithium-rich material 20, resulting in limited capacity, and will cause the conductivity of the composite lithium-supplementing material to decrease, which is not conducive to the release of lithium ions. When the mass proportion of the second functional material 30 is too small, it is difficult for the second functional material 30 to block the pores 11, which will increase the gas production of the material. Optionally, the mass ratio of the lithium-rich material 20, the first functional material 10 and the second functional material 30 can be, 20: (10-79): (1-10), 50: (10-79): (1-10), 80: (10-79): (1-10), (20-80): 10: (1-10), (20-80): 40: (1-10), (20-80): 79: (1-10), (20-80): (10-79): 1, (20-80): (10-79): 5, (20-80): (10-79): 10.

[0081] This application provides a method for preparing a composite lithium supplement material. Please refer to Figure 6 .

[0082] In one embodiment, the preparation method of the composite lithium supplement material comprises the following steps:

[0083] Step S10, coating the first functional material outside the template material, and then removing the template material to obtain the first functional material with pores, the pores extending to the outer surface of the first functional material to form openings.

[0084] Step S20, sequentially mix and sinter the first functional material, the lithium-rich material precursor and the second functional material precursor, so that the lithium-rich material precursor and the second functional material precursor are respectively converted into the lithium-rich material and the second functional material in the pores, the second functional material is a porous structure, and the second functional material is arranged between the lithium-rich material and the opening of the pores.

[0085] Optionally, in step S10, the template material includes one or more of nano-gold, nano-silver, and nano-carbon nitride. The first functional material can refer to the above-mentioned embodiment, and will not be described in detail here. It is understandable that after the first functional material coats the template material and the template material is removed, since the structure of the first functional material is not affected, a pore can be formed inside the first functional material.

[0086] In one embodiment, in step S20, the first functional material, the lithium-rich material precursor, and the second functional material precursor are sequentially mixed and sintered, specifically comprising the following steps:

[0087] Step S21, mixing the first functional material and the lithium-rich material precursor so that the lithium-rich material precursor is contained in the pores, and converting the lithium-rich material precursor into the lithium-rich material through sintering or drying steps.

[0088] Step S22, mixing the first functional material having lithium-rich material and the second functional material precursor so that the second functional material precursor is accommodated in the pores, and converting the second functional material precursor into the second functional material through sintering or drying steps.

[0089] Optionally, in step S21, the lithium-rich material precursor includes an inorganic metal salt or an organic metal salt, etc.; of course, the lithium-rich material precursor may also include an organic lithium salt, etc., such as lithium carbonate, lithium oxalate, etc., which can be directly used as a lithium-rich material. In this step, the lithium-rich material precursor can be used to convert into the first lithium-rich material in the above embodiment.

[0090] Optionally, in step S22, the second functional material precursor includes inorganic silicon, organic silicon, etc., so as to prepare a porous silicon material; of course, the second functional material precursor may also include small molecule organic matter, high molecular organic matter, etc., so as to prepare a porous carbon material.

[0091] Optionally, in step S22, the second functional material precursor may be added to the pores by a solution mixing method, a vapor deposition method or the like, and the second functional material may be formed in the pores by in-situ sintering.

[0092] In one implementation, please refer to Figure 5 and Figure 6 In the case where the composite lithium supplement material includes a core, the preparation method of the composite lithium supplement material comprises the following steps:

[0093] Step S00, growing a template material on the outer surface of the inner core, and the template material is arranged radially on the outer surface of the inner core.

[0094] Optionally, in step S00, the core includes the materials provided in the above-mentioned embodiments, which are not described in detail here. The template material can be grown on the outer surface of the core by chemical vapor deposition, and the template material grows in an island shape, and the volume of the template material at one end away from the core decreases. In this step, the material for preparing the core may include the second lithium-rich material in the above-mentioned embodiment.

[0095] Of course, in step S10 after step S00, the first functional material should be coated outside the core with the template material. And after the template material is removed, radially distributed channels with the core as the center are formed in the first functional material.

[0096] The present application provides a method for preparing a composite lithium-supplementing material, wherein a pore is made inside a first functional material through a template material, and a lithium-rich material and a second functional material are accommodated in the pore, and the pore is blocked by the second functional material, and the lithium-rich material can be protected by the first functional material to avoid side reactions between the lithium-rich material and an electrolyte or air; and the first functional material has conductivity, which can improve the conductivity of the material as a whole, does not affect the capacity release of the lithium-rich material, and can also maintain the structural stability of the electrode to prevent pits and cracks; in addition, the second functional material is used to block the opening of the pore, so that the gas generated after the lithium-rich material is discharged is confined in the pore, thereby reducing the gas production of the composite lithium-supplementing material.

[0097] In one embodiment, the present application further provides a positive electrode material, the positive electrode material comprising a positive electrode active material and a lithium supplement. The lithium supplement is a composite lithium supplement material provided in the above embodiment. Optionally, the positive electrode active material can be a phosphate positive electrode active material or a ternary positive electrode active material. In a specific embodiment, the positive electrode active material comprises one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium vanadium phosphate fluoride, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

[0098] In one embodiment, the content of the composite lithium-supplementing material in the positive electrode material can be controlled at 1% to 6% of the mass of the positive electrode active material. This ratio can just make up for the loss of active lithium in the battery during the first charging process. If the amount of composite lithium-supplementing material added to the positive electrode material is too low, the active lithium lost in the positive electrode active material cannot be fully replenished, which is not conducive to improving the energy density and capacity retention rate of the battery. If the amount of composite lithium-supplementing material added to the positive electrode active material is too high, the original reversible capacity will be occupied and the cost will be increased. In some specific embodiments, in the positive electrode material, the mass percentage of the composite lithium-supplementing material can be 1%, 2%, 4%, 6%, etc.

[0099] In one embodiment, the present application further provides a positive electrode plate, the positive electrode plate includes a current collector and an active material layer disposed on the current collector, the active material layer includes the composite lithium supplement material of any one of the above embodiments. Or the active material layer includes the composite lithium supplement material obtained by the preparation method of the composite lithium supplement material in the above embodiments.

[0100] In one embodiment, the positive electrode sheet includes a positive current collector, and the positive current collector has a positive active layer, and the positive active layer includes components such as positive active materials, composite lithium supplement materials, conductive agents, and binders. The present application does not specifically limit these materials, and suitable materials can be selected according to actual application requirements. The positive current collector includes but is not limited to any one of copper foil and aluminum foil. The conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes, and the content of the conductive agent in the positive active layer is 3wt% to 5wt%. The types of binders include polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, and the content of the binder in the positive active layer is 2wt% to 4wt%.

[0101] In one embodiment, the present application also provides a secondary battery, which includes a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode includes the above-mentioned positive electrode material; the electrolyte can be an electrolyte solution, so the secondary battery also includes a diaphragm arranged between the positive electrode plate and the negative electrode plate; or, the electrolyte can be a solid electrolyte solution, so the secondary battery does not have a diaphragm and is replaced by a solid electrolyte.

[0102] In one embodiment, after the secondary battery is charged and discharged for the first time, in the composite lithium supplement material, the outer surface of the second functional material is in contact with the side wall of the pore.

[0103] The technical solution of the present application is described in detail below through specific embodiments.

[0104] Example 1

[0105] This embodiment provides a composite lithium supplement material. The composite lithium supplement material includes a core (Li5FeO4, LFO), a first functional material (graphene), a first lithium-rich material (LiNiO2, LNO) and a second functional material (nano-silicon dioxide). The first functional material has a pore inside, and the pore is conical.

[0106] The particle size D50 of the inner core is 100nm, the thickness of the first functional material is 500nm, the mass ratio of the inner core and the first functional material is 20:80, the porosity of the first functional material is 30%, the inner diameter range of the pore is 50nm~80nm, the particle size of the second functional material is 25nm, the porosity of the second functional material is 30%, the expansion rate of the second functional material is 250%, and the mass ratio of the first lithium-rich material, the first functional material and the second functional material is 70:25:5.

[0107] The preparation method of the composite lithium supplement material comprises the following steps:

[0108] 1) Li5FeO4 is crushed into nanometer range by ball milling, and then placed in a tubular furnace. A mixed gas of CH4, H2, and NH3 is used as the deposition gas with a flow rate of 100 ml / min. A spiral tungsten wire is inserted into the tubular furnace. The distance between the tungsten wire and Li5FeO4 is 5 mm. The tungsten wire is heated to about 850°C, and the vacuum is evacuated to a total pressure of less than 2 Pa. Then, the reaction gas is introduced. When the pressure is greater than 3 KPa, the reaction is terminated to obtain a template material radially arranged on the surface of the Li5FeO4 core.

[0109] 2) ALD is used to coat graphene on the outside of the core with the template material, and the core is placed in an ALD chamber, which is evacuated to 0.1 torr, and 1 torr TMA is introduced. The reaction is carried out for 5 minutes, and nitrogen is purged for 30 minutes. Then, ozone is introduced for 6 minutes, and the reaction is carried out for 5 minutes. The nitrogen is purged for 30 minutes. This is one cycle, and the reaction is continuously repeated until the pressure in the chamber does not change when TMA is introduced in the next cycle. The reaction is completed and a spherical structure has been formed. The spherical structure is then sintered in the air, and the template material is removed by air ablation to form a small ball with a pore structure. The pore size of the small ball gradually decreases from the center of the sphere to the surface of the sphere, and the multiple pores are arranged radially.

[0110] 3) Hydroxylation is performed on the inner surface of the pores of the spheres, and the spheres are placed in an ALD chamber and evacuated to 0.1 torr. Mixed water vapor is then introduced for etching to bind hydroxyl groups to the surface of Li5FeO4. The introduction time is 20 seconds, wherein the mixed water vapor includes nitrogen and water vapor, and the water vapor content is 1 ppm. The flow rate of the mixed water vapor is 100 ml / min. ALD is then used to deposit Li2O2 and CoO, and the precursor is replaced by TMA with lithium tert-butoxide and Ni(CpMe)2 to in-situ form a precursor of LiNiO2. The precursor is then sintered in a tubular furnace at 750°C, an argon atmosphere flow rate of 400 ml / min, a heating rate of 2°C / min, and 4 hours to form LiNiO2.

[0111] 4) Using silane and nitrogen as precursors, a vapor phase chemical deposition method is used. At 800°C in a tube furnace, the gas flow rate is 100 ml / min, and the reaction time is 30 minutes. Silicon is added into the nanopores, and then nanoporous silica is formed by in-situ sintering in air, thereby finally forming a composite lithium supplement material.

[0112] Example 2

[0113] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the porosity of the first functional material is 5%.

[0114] Example 3

[0115] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the porosity of the first functional material is 40%.

[0116] Example 4

[0117] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the inner diameter of the pores ranges from 10 nm to 20 nm.

[0118] Example 5

[0119] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the inner diameter of the pores ranges from 90 nm to 100 nm.

[0120] Example 6

[0121] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the particle size of the second functional material is 1 nm.

[0122] Example 7

[0123] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the particle size of the second functional material is 50 nm.

[0124] Example 8

[0125] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the porosity of the second functional material is 5%.

[0126] Example 9

[0127] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the porosity of the second functional material is 40%.

[0128] Example 10

[0129] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the expansion rate of the second functional material is 150%.

[0130] Embodiment 11

[0131] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the expansion rate of the second functional material is 300%.

[0132] Example 12

[0133] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the mass ratio of the first lithium-rich material, the first functional material and the second functional material is 30:69:1.

[0134] Example 13

[0135] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the mass ratio of the first lithium-rich material, the first functional material and the second functional material is 70:20:10.

[0136] Embodiment 14

[0137] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the core is Ag.

[0138] Embodiment 15

[0139] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the first functional material is carbon.

[0140] Example 16

[0141] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the core is Li6CoO4, LCO.

[0142] Embodiment 17

[0143] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the second functional material is nano polyacrylic acid, PAA.

[0144] Embodiment 18

[0145] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that there is no core.

[0146] Embodiment 19

[0147] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the pores are not conical, the diameters of the pores are uniform, and the inner diameter of the pores is 60 nm.

[0148] Comparative Example 1

[0149] This comparative example provides a first lithium-rich material (LiNiO2).

[0150] Comparative Example 2

[0151] This comparative example provides a composite lithium supplement material. The difference between this comparative example and Example 1 is that the core, the first functional material, the first lithium-rich material and the second functional material are simply mixed.

[0152] Comparative Example 3

[0153] This comparative example provides a composite lithium supplement material. The difference between this comparative example and Example 1 is that the second functional material is not included.

[0154] The parameters of the composite lithium supplement materials provided by Examples 1 to 19 and Comparative Examples 1 to 3 are shown in Table 1:

[0155] Table 1 Parameters of composite lithium supplement materials provided in Examples and Comparative Examples

[0156]

[0157]

[0158] The composite lithium supplement materials provided in the above-mentioned Examples 1 to 19 and the composite lithium supplement materials provided in Comparative Examples 1 to 3 are respectively assembled into positive electrode sheets and lithium-ion batteries according to the following methods:

[0159] Positive electrode sheet: The composite lithium supplement material, SP and PVDF are mixed in a mass ratio of 90:4:6 to form a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet;

[0160] Negative electrode: lithium sheet;

[0161] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, and the concentration of LiPF6 was 1 mol / L;

[0162] Diaphragm: Polypropylene microporous separator;

[0163] Lithium-ion battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.

[0164] The electrochemical performance of each lithium-ion battery assembled in the above lithium-ion battery embodiment was tested under the following test conditions:

[0165] The battery was charged at a rate of 0.1C with a cut-off voltage of 4.7V; constant voltage charging was performed at a cut-off voltage of 4.7V; after the charging process was completed, the battery was allowed to stand for 10 minutes and then discharged at a rate of 0.1C with a cut-off voltage of 2.5V; the charging platform was observed during the charging process to obtain the decomposition voltage of the composite lithium supplement material; and the first cycle efficiency = (charge specific capacity / discharge specific capacity)*100%.

[0166] The gas production of each lithium-ion battery assembled in the above lithium-ion battery embodiment was tested under the following test conditions:

[0167] 1: Place the charged and discharged battery into the gas collection bag, break the battery open through the device inside the gas collection bag, and release the gas into the gas collection belt.

[0168] 2: Place the gas collection bag in contact with the syringe, put the gas collection bag into water, press the gas into the syringe with a pressure gauge, adjust the syringe so that the pressure gauge is maintained at atmospheric pressure, and read the syringe reading.

[0169] The above lithium battery test results are shown in Table 2 below:

[0170] Table 2. Test results of embodiments and comparative examples

[0171]

[0172] From the test results of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in Table 1, it can be seen that the composite lithium-supplementing material provided by the present application has a significantly lower charging voltage platform and gas production than ordinary lithium-rich materials (LNO), and the volume change rate of the pole piece is reduced. At the same time, compared to simply mixing lithium-rich materials and functional materials, the present application provides a composite lithium-supplementing material, and the functional material has a specific structure, which will reduce the internal resistance of the composite lithium-supplementing material, thereby increasing the capacity of the material and allowing the material to decompose completely. By adding a second functional material, the collapse of the composite lithium-supplementing material during the decomposition process can be avoided, the gas production of the material can be reduced, and the second functional material has an expansion effect during the charge and discharge process, which can reduce the volume change rate of the pole piece.

[0173] It can be seen from the test results of Example 1, Example 2, Example 3, Example 4 and Example 5 in Table 1 that the pore structure and porosity of the first functional material will affect the material performance. When the porosity is too small or the inner diameter of the pore is too small, too little lithium-rich material is contained, which will cause the capacity of the composite lithium-supplementing material to drop sharply. When the porosity is too large or the inner diameter of the pore is too large, the overall structure will fail, and the second functional material will not be able to effectively block the pore, resulting in the composite lithium-supplementing material having no effect of absorbing gas production, and at the same time causing an increase in the volume change rate of the pole piece.

[0174] From the test results of Example 1, Example 6, Example 7, Example 8, Example 9, Example 10 and Example 11 in Table 1, it can be seen that the particle size and expansion rate of the second functional material will affect the material performance. When the particle size is too small and the porosity is too large, there will be no plugging effect, the gas production will increase, and the pole piece change rate will increase. When the particle size is too large and the porosity is too small, the internal resistance of the material will increase, the lithium supplement material will not be completely decomposed, and the capacity and decomposition voltage of the material will increase. At the same time, the expansion rate of the second functional material is also critical. If the expansion rate is too small, the plugging effect will be poor and the effect of suppressing gas production will be poor. If the expansion rate is too large, the overall structure of the material will be destroyed during the lithium supplement process, the pole piece change rate will be too large, and even pits will appear.

[0175] From the test results of Example 1, Example 12, and Example 13 in Table 1, it can be seen that the mass ratio of the first lithium-rich material, the first functional material, and the second functional material will affect the material performance. When the mass ratio of the three is too small, the proportion of the lithium-rich material is too small. Although the decomposition voltage and gas production are small, the lithium replenishment capacity is too low and the lithium replenishment effect is too poor. When the mass ratio is too large, the proportion of the lithium-rich material is too large and the proportion of the functional material is too small, resulting in failure of the composite structure and poor effect of suppressing gas production and pole piece change rate.

[0176] From the test results of Example 1 and Example 14 in Table 1, it can be seen that when the core is a non-lithium-supplemented material, the capacity will be lower than that of a lithium-rich material, but the decomposition voltage will be lower, and the decomposition degree of the lithium-rich material will be higher, but both have similar effects of inhibiting the gas production of the lithium-supplemented material and inhibiting the change of the electrode structure. This also shows that the core provided by the present application can be replaced by a non-lithium-rich material.

[0177] From the test results of Example 1, Example 15, Example 16 and Example 17 in Table 1, it can be seen that when the first functional material uses ordinary carbon, or the first lithium-rich material is changed to LCO or the second functional material is changed to nano-polyacrylic acid, it has the same effect of inhibiting gas production and reducing the pole piece change rate. This shows that the function of the composite lithium supplement material comes from its composite structure and is not limited to a specific lithium-rich material.

[0178] It can be seen from the test results of Example 1 and Example 18 in Table 1 that if there is no core and step 1) is not performed, a conical channel cannot be formed, the composite structure cannot be formed, and the effect of suppressing the gas generated during the decomposition of the composite lithium supplement material and suppressing the change of the electrode structure is not achieved.

[0179] It can be seen from the test results of Example 1 and Example 19 in Table 1 that if the tapered pores are not used, the second functional material cannot block the pores, resulting in extremely poor effect of inhibiting gas production.

[0180] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0181] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A composite lithium supplement material, characterized in that: It includes a lithium-rich material, a first functional material and a second functional material. The first functional material has a pore inside, the pore extends to the outer surface of the first functional material and forms an opening, the second functional material and at least part of the lithium-rich material are accommodated in the pore, the second functional material is a porous structure, and the second functional material is arranged between the lithium-rich material and the opening of the pore.

2. The composite lithium supplement material according to claim 1, characterized in that: The pore size of the pores gradually decreases from the inside of the first functional material to the outer surface of the first functional material; and / or, there are multiple pores, and at least two of the pores have different pore sizes, and the particle sizes of the lithium-rich materials accommodated in the pores of different pore sizes are different; and / or, the same pore includes at least two lithium-rich materials, and the types and / or particle sizes of the two lithium-rich materials are different.

3. The composite lithium supplement material according to claim 1, characterized in that: The composite lithium supplement material further includes a core, the first functional material is coated on the outer layer of the core, and the core includes one or more of a lithium-rich material, a catalytic material, and a supporting material.

4. The composite lithium supplement material according to claim 3, characterized in that: The inner core comprises a lithium-rich material, the lithium-rich material contained in the pores is a first lithium-rich material, the lithium-rich material forming the inner core is a second lithium-rich material, and the second lithium-rich material is of a different type from the first lithium-rich material; the mass ratio of the first lithium-rich material to the second lithium-rich material is in the range of (50-95): (5-50).

5. The composite lithium supplement material according to claim 1, characterized in that: The inner diameter of the pores ranges from 10 nm to 100 nm; and / or The particle size of the second functional material is in the range of 1 nm to 50 nm; and / or The second functional material is at least partially attached to the sidewall of the pore; and / or The porosity of the second functional material is 20% to 60%; and / or The expansion rate of the second functional material is 150% to 300%; and / or The second functional material includes one or more of silicon material, carbon material, polymer material and gel material.

6. The composite lithium supplement material according to any one of claims 3 to 5, characterized in that: The particle size D50 of the core is 100nm to 500nm; and / or The thickness of the first functional material coated on the outer surface of the core is 100nm to 1500nm; and / or The first functional material comprises a carbon material and / or a metal oxide; and / or The porosity of the first functional material is 5% to 40%; and / or The mass ratio of the lithium-rich material, the first functional material and the second functional material is (20-80):(10-79):(1-10).

7. A method for preparing a composite lithium supplement material, characterized in that: The steps include: Coating a first functional material on the outer surface of the template material, and then removing the template material to obtain a first functional material having pores, wherein the pores extend to the outer surface of the first functional material and form openings; The first functional material, the lithium-rich material precursor and the second functional material precursor are sequentially mixed and sintered so that the lithium-rich material precursor and the second functional material precursor enter the pores and are respectively converted into the lithium-rich material and the second functional material, wherein the second functional material is a porous structure and is arranged between the lithium-rich material and the opening of the pores.

8. A positive electrode material, characterized in that The positive electrode material includes a positive electrode active material and a lithium supplement agent, and the lithium supplement agent includes the composite lithium supplement material according to any one of claims 1 to 6, or includes the composite lithium supplement material obtained by the preparation method of the composite lithium supplement material according to claim 7.

9. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material as claimed in claim 8.

10. The secondary battery according to claim 9, characterized in that: After the secondary battery is charged and discharged for the first time, in the composite lithium supplementing material, the outer surface of the second functional material is in contact with the side wall of the pore.